Mistletoe games - Burton, Jaci (Burton, Jaci. Play-by-play novel., 2016)
Holiday games -- "For the high-achieving Elizabeth and her husband, baseball player Gavin Riley, failure is not an option. So when it comes to making a baby, they're not about to let any holiday distractions get in the way of their necessary pleasures"--Back cover.